Euphemia and speech events - Shohistaxon Qudratullaevna Shamsieva (International Journal on Orange Technologies, 2020)
An event that occurs in the presence of euphemistic means is a phenomenon of euphemism. The first factor in the occurrence of this phenomenon is the use of another word (or phrase) instead of taboo words. Stylistics or rhetoric (rhetoric) also explores the use of words and phrases interchangeably. But in these fields of science there are also phenomena, methodological figures, which in some respects resemble the phenomenon we are studying as a euphemism, which can also be the object of study in the field of linguistics. We have sought to shed light on phenomena similar in some respects to euphemism in order to further clarify our views on euphemism and euphemism.